2022
DOI: 10.1177/10775595221134248
|View full text |Cite
|
Sign up to set email alerts
|

From Maltreatment to Psychiatric Disorders in Childhood and Adolescence: The Relevance of Emotional Maltreatment

Abstract: Different forms of maltreatment are thought to incur a cumulative and non-specific toll on mental health. However, few large-scale studies draw on psychiatric diagnoses manifesting in early childhood and adolescence to identify sequelae of differential maltreatment exposures, and emotional maltreatment, in particular. Fine-grained multi-source dimensional maltreatment assessments and validated age-appropriate clinical interviews were conducted in a sample of N = 778 3 to 16-year-olds. We aimed to (a) substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 70 publications
4
6
0
1
Order By: Relevance
“…When looking at separate adversity types it was observed that the negative association between childhood adversity and global self‐esteem was only statistically significant for emotional neglect and abuse. This is also consistent with the existing literature, which finds similar results (Babad et al, 2020; Reid‐Russell et al, 2021; Schlensog‐Schuster et al, 2022). One possible explanation might lie in attachment theory (Bowlby, 1969).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When looking at separate adversity types it was observed that the negative association between childhood adversity and global self‐esteem was only statistically significant for emotional neglect and abuse. This is also consistent with the existing literature, which finds similar results (Babad et al, 2020; Reid‐Russell et al, 2021; Schlensog‐Schuster et al, 2022). One possible explanation might lie in attachment theory (Bowlby, 1969).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, several studies have demonstrated a negative effect of childhood adversity via self‐esteem on several different psychiatric symptoms (Berber Çelik & Odacı, 2020; Ju & Lee, 2018). Particularly childhood emotional abuse and neglect seem to be the most poignant contributing factors (Reid‐Russell et al, 2021; Schlensog‐Schuster et al, 2022). Second, the relationship between self‐esteem and psychiatric symptoms may be bidirectional.…”
Section: Introductionmentioning
confidence: 99%
“…In the ADHD group, children of mothers with a lower education level and higher depressive symptoms showed lower HCC. This corresponds to the findings of studies by White et al [21,53] on children/adolescents with externalizing disorders: low HCC was found in children with externalizing disorders who experienced (emotional) maltreatment. Maternal depressive symptoms may reflect family adversity and indicate less adequate parenting, thus potentially chronic ACE, which in turn leads to low HCC in the child [10].…”
Section: Discussionsupporting
confidence: 90%
“…Considering maltreatment could be particularly elucidating (see e.g. [21,53,57]). Finally, in future studies, it may be illuminating to analyze further hormones (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Hett et al 2022, 128 one possible explanation for this is that sexual and physical abuse typically also involve emotional abuse, either predating it or being part of it. In turn, there is a substantial body of evidence demonstrating that emotional abuse may be more strongly associated with high levels of affective instability, 129,130 emotional dysregulation, 131,132 internalising and externalising disorders, 133 factors that may mediate the relationship between CM and social features of AD. Taken together, our findings indicate that emotional abuse represents an important potential therapeutic target for AD.…”
Section: Discussionmentioning
confidence: 99%